Controversies around the Quality of Comprehensive Income Information Presented by Business Entities - Poniatowska, Lucyna; Rówińska-Kral', Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The article assesses the current way of presenting achievements (measured by comprehensive income) by selected joint-stock companies in the statement of financial position. This is done in the light of the concept of comprehensive income and the comparability and understandability of financial information. The article also presents the authors’ solution for presenting comprehensive income.Research Design & Methods: The research method used in the theoretical part is a critical analysis of IFRS regulations (in particular IAS 1) and the literature thereof. The empirical part uses financial statements prepared for 2022 by selected companies listed on the Warsaw Stock Exchange. On the basis of those, a critical assessment of the information presented on comprehensive income and its components is presented.Findings: The research shows the lack of uniform solutions in the presentation of comprehensive income, especially in the context of the statement of financial position. The effect of such a state of affairs is the low quality of reporting information, and thus the limited readability of reports and the usability of information for stakeholders.Implications / Recommendations: Presenting the value of the profit or loss and other comprehensive income directly in the structure of equity should be made obligatory. This would increase the readability of information on comprehensive income, and reduce the ambiguity stakeholders face in interpreting it. It would also ensure a close link between the elements of the financial statements, the layout of which is partly based on the concept of comprehensive income.Contribution: The authors’ solution for presenting comprehensive income in the statement of financial position is the main contribution.